Comparison of Adverse Kidney Outcomes With Empagliflozin and Linagliptin Use in Patients With Type 2 Diabetic Patients in a Real-World Setting - Yueh-Ting Lee; Chien-Ning Hsu; Chien-Ning Hsu; Chung-Ming Fu; Shih-Wei Wang; Chiang-Chi Huang; Lung-Chih Li; Lung-Chih Li (Frontiers Media S.A., 2021)
Background: To compare the effects of empagliflozin and linagliptin use on kidney outcomes of type 2 diabetes mellitus (T2DM) patients in a real-world setting.Methods: The study involved a propensity score-matched cohort comprising new users of empagliflozin or linagliptin with T2DM between January 1, 2013 and December 31, 2018 from a large healthcare delivery system in Taiwan. Clinical outcomes assessed: acute kidney injury (AKI), post-AKI dialysis, and mortality. Cox proportional hazard model was used to estimate the relative risk of empagliflozin or linagliptin use; a linear mixed model was used to compare the average change in estimated glomerular filtration rate (eGFR) over time.Results: Of the 7,042 individuals, 67 of 3,521 (1.9%) in the empagliflozin group and 144 of 3,521 (4.1%) in the linagliptin group developed AKI during the 2 years follow-up. Patients in the empagliflozin group were at a 40% lower risk of developing AKI compared to those in the linagliptin group (adjusted hazard ratio [aHR], 0.60; 95% confidence interval [CI], 0.45-0.82, p = 0.001). Stratified analysis showed that empagliflozin users ≥65 years of age (aHR, 0.70; 95% CI, 0.43-1.13, p = 0.148), or with a baseline eGFR <60 ml/min/1.73 m2 (aHR, 0.97; 95% CI, 0.57-1.65, p = 0.899), or with a baseline glycohemoglobin ≦7% (aHR, 1.01; 95% CI, 0.51-2.00, p =0.973) experienced attenuated benefits with respect to AKI risk. A smaller decline in eGFR was observed in empagliflozin users compared to linagliptin users regardless of AKI occurrence (adjusted β = 1.51; 95% CI, 0.30-2.72 ml/min/1.73 m2, p = 0.014).Conclusion: Empagliflozin users were at a lower risk of developing AKI and exhibited a smaller eGFR decline than linagliptin users. Thus, empagliflozin may be a safer alternative to linagliptin for T2DM patients.